2010
DOI: 10.3390/ma3021186
|View full text |Cite
|
Sign up to set email alerts
|

The One-Step Pickering Emulsion Polymerization Route for Synthesizing Organic-Inorganic Nanocomposite Particles

Abstract: Polystyrene-silica core-shell nanocomposite particles are successfully prepared via one-step Pickering emulsion polymerization. Possible mechanisms of Pickering emulsion polymerization are addressed in the synthesis of polystyrene-silica nanocomposite particles using 2,2-azobis(2-methyl-N-(2-hydroxyethyl)propionamide (VA-086) and potassium persulfate (KPS) as the initiator. Motivated by potential applications of “smart” composite particles in controlled drug delivery, the one-step Pickering emulsion polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 54 publications
0
38
0
1
Order By: Relevance
“…After the exhaustion of monomers in the droplets, the nano-SiO 2 initially adsorbed at droplets interfaces might re-disperse in the aqueous phase gradually, and some of them would self-assemble at the surfaces of the newly created polystyrene microspheres. However, it is likely due to the steric hindrance of nanoparticles or the repulsive interaction between the anionic initiator residues and the negatively charged nano-SiO 2 [35], the polystyrene microspheres are barely covered with silica nanoparticles and show loose core-shell morphology.…”
Section: Mechanism Analysis Of Ps/sio 2 Composite Microspheres Preparmentioning
confidence: 99%
“…After the exhaustion of monomers in the droplets, the nano-SiO 2 initially adsorbed at droplets interfaces might re-disperse in the aqueous phase gradually, and some of them would self-assemble at the surfaces of the newly created polystyrene microspheres. However, it is likely due to the steric hindrance of nanoparticles or the repulsive interaction between the anionic initiator residues and the negatively charged nano-SiO 2 [35], the polystyrene microspheres are barely covered with silica nanoparticles and show loose core-shell morphology.…”
Section: Mechanism Analysis Of Ps/sio 2 Composite Microspheres Preparmentioning
confidence: 99%
“…Pickering emulsions can be used to synthesize core-shell nanocomposite particles, where the polymer serves as the core and inorganic particle serve as the shell [79]. Such materials provide a new class of supramolecular building blocks, exhibiting unusual, unique properties with potential applications in drug and gene deliveries, enzyme immobilization, colloidal nanocatalysts, chemical sensing, functional coating.…”
Section: Smart Emulsionsmentioning
confidence: 99%
“…Figure 5 shows the dependence of particle size and surface coverage on reaction time and initiator concentration [Ma et al, 2010]. The composite particles are sampled from 3 h to 24 h reaction time and the initiator concentration relative to monomer is selected to be 0.83, 2.5, and 4.2 wt % respectively.…”
Section: Possible Mechanisms Of Pickering Emulsion Polymerizationmentioning
confidence: 99%
“…Such materials provide a new class of supramolecular building blocks and can "exhibit unusual, possibly unique, properties which cannot be obtained simply by co-mixing polymer and inorganic particles." (Barthet et al, 1999) In comparison with the recently reported methods to synthesize core-shell composite particles, for example, post-surface-reactio (Ding et al, 2004;Lynch et al, 2005), electrostatic deposition (Dokoutchaev et al, 1999), and layer-by-layer self-assembly (Caruso, 2001;Caruso et al, 1999;Caruso et al, 2001), we synthesize core-shell composite nanoparticles through a novel Pickering emulsion polymerization route (Ma and Dai, 2009;Ma et al, 2010). Figure 1 illustrates the polymerization route and its comparison with the conventional emulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%